1998
DOI: 10.1097/00006534-199808000-00031
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Harvesting of Jejunal Free Flaps for Esophageal Reconstruction

Abstract: Endoscopic harvest of the jejunum is indicated for the reconstruction of complex defects of the head and neck and specifically the reconstruction of circumferential defects of the esophagus. However, open laparotomies are associated with systemic and local morbidity and are often seen as prohibitively invasive procedures. Laparoscopy for intra-abdominal procedures is a proven technique that yields less morbidity and provides an anatomical exposure similar to that of the open approach. We report on 11 consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 8 publications
0
14
0
2
Order By: Relevance
“…42 However, it took 3 hours, on average, in that study to harvest jejunal flaps, even with a single pedicle. 42 However, it took 3 hours, on average, in that study to harvest jejunal flaps, even with a single pedicle.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…42 However, it took 3 hours, on average, in that study to harvest jejunal flaps, even with a single pedicle. 42 However, it took 3 hours, on average, in that study to harvest jejunal flaps, even with a single pedicle.…”
Section: Discussionmentioning
confidence: 93%
“…A previous report of laparoscopic harvest of jejunal flaps suggested that it was less invasive than the regular open laparotomy harvest. 42 However, it took 3 hours, on average, in that study to harvest jejunal flaps, even with a single pedicle. In our procedure, multiple jejunal vessels and arcade vessels must be dissected, and, therefore, performing our procedure laparoscopically would be too time-consuming.…”
Section: Discussionmentioning
confidence: 93%
“…Traditionally, the flap is harvested through a midline incision. Recently there has been increased interest in laparoscopic flap harvest, 83 which can decrease abdominal pain, recovery time, and morbidity associated with the harvest. Transillumination of the bowel aids in identification of the vascular arcades.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Es können bis zu 30 cm lange Jejunumsegmente gehoben werden [9,23], die aus einer Gefäûarkade versorgt werden. Diese Transplantate wurden im vorliegenden Patientengut unter Erhaltung der Gefäûarkaden geteilt, so daû bis zu 3 Darmsegmente für eine Defektdeckung zur Verfügung standen.…”
Section: Deckung Von Haut-weichteildefektenunclassified
“…Nach experimentellen Studien bei Schweinen und Hunden [27] haben Gherardini et al [9] ein entsprechendes Verfahren beschrieben und bei 10 Patienten eingesetzt. Nach experimentellen Studien bei Schweinen und Hunden [27] haben Gherardini et al [9] ein entsprechendes Verfahren beschrieben und bei 10 Patienten eingesetzt.…”
Section: Deckung Von Haut-weichteildefektenunclassified